Efficacy and safety of iron isomaltoside (Monofer®) in the management of patients with iron deficiency anemia - Kalra PA; Bhandari S (International Journal of Nephrology and Renovascular Disease, 2016)
Philip A Kalra,1 Sunil Bhandari2,31Department of Renal Medicine, Salford Royal NHS Foundation Trust, Salford, UK; 2Hull and East Yorkshire Hospitals NHS Trust, Hull, UK; 3Hull York Medical School, Hull, UKAbstract: New intravenous (IV) iron preparations should ideally be capable of delivering a wide dosing range to allow iron correction in a single or low number of visits, a rapid infusion (doses up to 1,000 mg must be administered over more than 15 minutes and doses exceeding 1,000 mg must be administered over 30 minutes or more), and minimal potential side effects including low catalytic/labile iron release with minimal risk of anaphylaxis. Furthermore, they should be convenient for the patient and health-care professional, and cost effective for the health-care system. The intention behind the development of iron isomaltoside (Monofer®) was to fulfill these requirements. Iron isomaltoside has been shown to be effective in treating iron deficiency anemia across multiple therapeutic patient groups and compared to placebo, IV iron sucrose, and oral iron. Iron isomaltoside consists of iron and a carbohydrate moiety where the iron is tightly bound in a matrix structure. It has a low immunogenic potential, a low potential to release labile iron, and does not appear to be associated with clinically significant hypophosphatemia. Due to the structure of iron isomaltoside, it can be administered in high doses with a maximum single dosage of 20 mg/kg body weight. Clinical trials and observational studies of iron isomaltoside show that it is an effective and well-tolerated treatment of anemia across different therapeutic areas with a favorable safety profile.Keywords: iron deficiency anemia, iron isomaltoside, high dose, iron treatment, hypophosphatemia, intact fibroblast growth factor 23